Ataxie cérebelleuse épidémique au Nord du Bénin - JOSSE, Roger Gérard; COMLANVI, C; Houinato, Dismand; LAMMIE, J; FOUNDOHOU, J; COURATIER, P; DUMAS, M (My University, 1994)
Poster présenté au "Deuxième Congrès de Neurologie Tropicale"